2005
DOI: 10.1299/jsmeb.48.136
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Pressure Fluctuations and Vibration of the Impeller in a Centrifugal Pump with Vaned Diffusers

Abstract: The pressure fluctuations acting on the impeller and the impeller vibration excited by the fluctuations were investigated in a centrifugal pump with several vaned diffusers. Firstly, the pressures both acting on the impeller and in the volute were measured simultaneously. It was demonstrated that both the volute static pressure and the pressure fluctuations on the impeller are uneven circumferentially (not uniform) under off-design operating conditions. At high flow rates, the pressure fluctuations are large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Shi and Tsukamoto [9] studied pressure fluctuations in the diffuser region by a CFD code STAR-CD. Furthermore, experiments were conducted to measure pressure fluctuations in diffuser radial pumps by Arndt et al [10,11], Furukawa et al [12], Guo and Maruta [13]. All the above-mentioned experimental and numerical investigations contribute to a better understanding of impeller-diffuser interactions in radial diffuser pumps; however the study is still not sufficient; particularly, most research on the unsteady pressure fluctuation has been conducted only in the diffuser region, but less for the impeller region.…”
Section: Introductionmentioning
confidence: 99%
“…Shi and Tsukamoto [9] studied pressure fluctuations in the diffuser region by a CFD code STAR-CD. Furthermore, experiments were conducted to measure pressure fluctuations in diffuser radial pumps by Arndt et al [10,11], Furukawa et al [12], Guo and Maruta [13]. All the above-mentioned experimental and numerical investigations contribute to a better understanding of impeller-diffuser interactions in radial diffuser pumps; however the study is still not sufficient; particularly, most research on the unsteady pressure fluctuation has been conducted only in the diffuser region, but less for the impeller region.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that vibration signals caused by hydraulic factors mainly concentrate in low frequency band [22][23][24]. So vibration signals in low frequency band of two model pumps were investigated to analyze influence of slope volute on vibration characteristic in centrifugal pump.…”
Section: Vibration Characteristics Comparision Of Two Pumpsmentioning
confidence: 99%
“…Too large vibration will affect the reliability of pump operation. Therefore, measures should be taken to reduce the pressure fluctuation in the pump [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%